Nutritional interventions in pancreatic cancer: a systematic review - Emanuel, Aline; Krampitz, Julia; Rosenberger, Friederike; Kind, Sabine; Rötzer, Ingeborg (Cancers, 2022)
(1) Background: Pancreatic cancer (PaCa) is directly related to malnutrition, cachexia and weight loss. Nutritional interventions (NI) are used in addition to standard therapy. The aim of this systematic review is to provide an overview of the types of NI and their effects. (2) Methods: We included RCTs with at least one intervention group receiving an NI and compared them with a control group with no NI, placebo or alternative treatment on cachexia, malnutrition or weight loss in patients with PaCa. Any available literature until 12 August 2021 was searched in the Pubmed and Cochrane databases. RCTs were sorted according to NI (parenteral nutrition, enteral nutrition, dietary supplements and mixed or special forms). (3) Results: Finally, 26 studies with a total of 2720 patients were included. The potential for bias was mostly moderate to high. Parenteral nutrition is associated with a higher incidence of complications. Enteral nutrition is associated with shorter length of stay in hospital, lower rate and development of complications, positive effects on cytokine rates and lower weight loss. Dietary supplements enriched with omega-3 fatty acids lead to higher body weight and lean body mass. (4) Conclusions: Enteral nutrition and dietary supplements with omega-3 fatty acids should be preferred in nutritional therapy of PaCa patients.